Original papersSelf-reported depression and sense of disease in cosmetic patients - Magdziarz-Orlitz, Joanna; Gerlicz-Kowalczuk, Zofia A.; Dziankowska-Bartkowiak, Bożena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : An increasing number of patients with various personality disorders, psychological problems and depression due to real or imaginary cosmetic defects visit a doctor. Aim : Evaluation of the relationship between cosmetic problems and self-reported depression in individuals electing to undergo cosmetic procedures, sense of disease in these individuals as well as the relationship between self-reported disease and depression. Material and methods : Investigations using Beck Depression Inventory (BDI) and Self-Esteem Scale (SES) were carried out on 167 patients, before and 4 weeks after the procedure. Results : There is a statistically significant difference (p < 0.001) between mean values of measurements before (9.3 points) and after (6.12 points) surgical procedures. The percentage of patients with different severity of depression before the procedure decreased from 42% to 18%. Using SES, the problem was assessed in the following categories: Obstacle, Challenge, Threat, Injustice, Benefit and Importance. The difference between mean scores before and following the intervention was 6.52 points and was statistically significant (p < 0.05). Conclusions : The results obtained confirm that depression has an impact on self-reported disease and in the case of the investigated group it may be assumed that the aesthetic defect is a disease.